Ekstraksi Senyawa Antibakteri dari Chlorella Sp. - Max R. Wenno; Ninik Purbosari; Johanna L. Thenu (Politeknik Negeri Lampung., 2010)
Some bioactive compounds are produced by microalgae. One of them is antibacterial compounds that produced by Chlorella sp which is result of secondary metabolit. This compound called Chlorellin which is mixed of fatty acid. The experiment was conducted to extraction of bioactive compound and was knew antibacterial activity of Chlorella sp. Based to antibacterial activity assay, the crude extract of Chlorella sp. has been pursued growth of sampel bacteria : E.coli, S.aureus, A.hydophyla, P. Aeruginosa and V. Harveyi. This antibacterial activity marked with the forming of transparent zona is around paper disc on the agar media. Keywords: Chlorella, extraction, antibacterial compound